Books Published by Jack Kahane and the Obelisk Press. (Obelisk: A History of Jack Kahane & the Obelisk Press, 2007)
A list of books published by Jack Kahane and the Obelisk Press which include "Sleeveless Errand," by Norah James, "Joseph Hemard," by Marcel Valotaire, "Haveth Childers Everywhere," by James Joyce is presented.